Impact of sonication on activated sludge properties and consequences on PAH partitioning. (30th December 2015) - Mozo, Irene; Lesage, Nicolas; Sperandio, Mathieu; Bessiere, Yolaine
Abstract: Sonication is an efficient sludge disintegration technique that can be used for reducing the excess sludge produced in water treatment. The effects of activated sludge sonication on its physicochemical properties and their consequences on the partitioning of hydrophobic polycyclic aromatic hydrocarbons (PAH) are reported. Ultrasound treatment led to an increase in dissolved and colloidal matter in the aqueous phase, with a predominance of proteins compared to the initial supernatant. This transfer of DCM was found to be directly correlated to the energy applied, and resulted in proportional transfer of PAHs from the particulate phase to the aqueous fraction. The PAH aqueous fraction, initially ranging from 0.012 g/g (pyrene) to 0.19 g/g (naphthalene), reached between 0.25–0.37 g/g when a specific energy of 40 000 kJ/kgTS0 was applied. For the raw sludge, the logarithm of the equilibrium constant varied between 3.0–4.3, depending on the hydrophobicity of the molecule, but when sonication was applied, the affinity for particles decreased significantly, resulting in a narrow distribution (log KG  = 2.8–3.0 after 40 000 kJ/kgTS0 was applied). PAH partition is governed by molecule hydrophobicity (log Kow) for raw sludge and by sonication intensity for sonicated sludge.